Coping With the Gods - Versnel, H.S (Religions in the Graeco-Roman World, 2011)
Inspired by a critical reconsideration of current monolithic approaches to the study of Greek religion, this book argues that ancient Greeks displayed a disquieting capacity to validate two (or more) dissonant, if not contradictory, representations of the divine world in a complementary rather than mutually exclusive manner. From this perspective the six chapters explore problems inherent in: order vs. variety/chaos in polytheism, arbitrariness vs. justice in theodicy, the peaceful co-existence of mono- and polytheistic theologies, human traits in divine imagery, divine omnipotence vs. limitation of power, and ruler cult. Based on an intimate knowledge of ancient realia and literary testimonia the book stands out for its extensive application of relevant perceptions drawn from cultural anthropology, theology, cognitive science, psychology, and linguistics.